Heavy Metals Release in Soils - Selim, H. Magdi (CRC Press, 2009)
Understanding the mechanisms associated with metal complexes and the sequestering metal contaminants in the environment is essential for effective remediation. Heavy Metal Release in Soils describes and quantifies desorption/release kinetics and dissolution reactions in the release of heavy metals from soil. The book focuses on: New techniques - microscopic surface techniques, NMR and electrophoresis, XAFS, SFM, and time-resolved ATR-FTIR Theoretical analysis and kinetic approaches - adsorption/desorption hysteresis, competitive sorption and transport, multi-component models, speciation kinetics, isotherms and soil and metal parameters, and the role of soil properties on transport Applications - arsenic speciation and mobility in contaminated soils, modeling activity of CD, Zn, and Cu in contaminated soils, and in situ chemical immobilization A timely addition to the literature, this book highlights the desorption/release mechanisms for the purpose of resolving remediation dilemmas in contaminated environments. It gives you the added advantage of case studies at both the microscopic and macroscopic scales, and provides both experimental and numerical investigations. With contributions from an international panel of authors, Heavy Metals Release in Soils fills a gap in the current literature concerned with subsurface contaminant fate and transport processes.